The potency of Sansevieria trifasciata and S. cylindrica leaves extracts as an antibacterial against Pseudomonas aeruginosa - Whika Dewatisari; Laurentius Hartanto Nugroho; Endah Retnaningrum; Yekti Asih Purwestri (Society for Indonesian Biodiversity, 2021)
Abstract. Nugroho LH, Dewatisari WF, Retnaningrum E, Purwestri YA. 2021. The potency of Sansevieria trifasciata and S. cylindrica leaves extracts as an antibacterial against Pseudomonas aeruginosa. Biodiversitas 22: 408-415. Sansevieria trifasciata and Sansevieria cylindrica are the major herbs in Indonesia, which contain several bioactive compounds as potential sources of antibacterial agents. This study aims to evaluate the antibacterial activity of S. trifasciata and S. cylindrica leaves extract and fraction against Pseudomonas aeruginosa and to identify its bioactive compounds. Crude ethanolic extract of S. trifasciata and S. cylindrica leaves were tested for their antimicrobial activity by disk diffusion method against P. aeruginosa. S. trifasciata showed strong antibacterial activity with an inhibition zone of 18.3 mm compared to S. cylindrica. Different concentrations of extract i.e. 4 mg/mL, 8 mg/mL, 16 mg/mL, 32 mg/mL, 64 mg/mL, 128 mg/mL and 256 mg/mL were tested for their minimum inhibitory concentrations (MIC). The MIC results showed that the S. trifasciata extract was able to inhibit bacterial growth at a concentration of 32 mg/mL. Results of vacuum liquid chromatography (VLC) and thin-layer chromatography (TLC) revealed that only fraction 3 showed the highest antibacterial activity at 16 mg/mL. In TLC bioautography analysis, fraction 3 showed a clear zone at Rf 0.93. The phytochemical analysis showed that terpenoid, phenolic, triterpenoid, and flavonoid compounds were found in S. trifasciata extract that were associated with antibacterial activity.